Determinants of early neonatal mortality: secondary analysis of the 2012 and 2017 Indonesia Demographic and Health Survey - Christiana Rialine Titaley; Anifatun Mu'asyaroh; Bertha Jean Que; Dwi Hapsari Tjandrarini; Iwan Ariawan (Frontiers Media S.A., 2024)
BackgroundMost neonatal deaths occur during the first week of life (i.e., early neonatal deaths). In this analysis, we aimed to investigate the determinants of early neonatal deaths in a nationally representative sample of births in Indonesia over the five years before each survey.MethodsData were obtained from the 2012 and 2017 Indonesia Demographic and Health Survey (IDHS), including information from 58,902 mothers of children aged <5 years of age. The outcome variable was early neonatal death (death of a newborn within the first six days of life). Explanatory variables were categorized into environmental, household, maternal, pregnancy, childbirth, and child characteristics. Multivariate regression methods were employed for analysis.ResultsIncreased odds of early neonatal deaths were associated with mothers who lacked formal education or had incomplete primary schooling (adjusted odd ratio [OR] = 2.43, 95% confidence interval [CI]: 1.18-5.01), worked outside the house in agricultural (aOR = 5.94, 95% CI: 3.09-11.45) or non-agricultural field (aOR = 2.98, 95% CI: 1.88-4.72), and were required to make a joint decision about health care with their partner or another household member (aOR = 1.79, 95% CI: 1.12-2.84). Increased odds were also observed in smaller-than-average infants, particularly those who received low-quality antenatal care services (aOR = 9.10, 95% CI: 5.04-16.41) and those whose mothers had delivery complications (aOR = 1.72, 95% CI: 1.10-2.68) or who were delivered by cesarean section (aOR = 1.74, 95% CI: 1.07-2.82). Furthermore, male infants showed higher odds than female infants (aOR = 1.85, 95% CI: 1.23-2.76).ConclusionsA multifaceted approach is essential for curtailing early neonatal mortality in Indonesia. Enabling workplace policies, promoting women's empowerment, strengthening the health system, and improving the uptake of high-quality antenatal care services are among the critical steps toward preventing early neonatal deaths in Indonesia.